PENGARUH PENERAPAN SISTEM E-FILING DAN E-BILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA BATAM - Tipa, Handra; Azra, Lia Novita (LPPM Universitas Putera Batam, 2019)
In Indonesia taxpayers are authorized to calculate, store and report their own tax obligations. This study aims to determine the differences in e-filing (X1) with the WPOP (Y) agreement and e-billing adjustment (X2) on WPOP mediation (Y). The data of this study add primary data obtained through questionnaires to respondents registered at KPP Pratama Batam North uses the simple random sampling method. The population of this study is the WPOP of 208,905 taxpayers. The sample used in this study amounted to 100. Questionnaire data were tested by Validity Test, Reliability Test, Classical Assumption Test, and Hypothesis Test. All of these trials use the SPSS version 22 program. The results of this study indicate e-filing (X1) has a significant influence on WPOP (Y). This is evidenced by the t test which produces a tcount greater than the tcount (7.253> 1.988) and a significance value of 0.00 <0.05. And e-billing (X2) is strongly related to WPOP (Y) approval. This is proven by the t test which produces a value of t count greater than the value of t table (4.439> 1.988) and a significance value of 0.00 <0.05. So the government prefers to socialize the e-filing and e-billing system to WPOP.